Local Perceptions of Climate Change Impacts in St. Kitts (Caribbean Sea) and Malé, Maldives (Indian Ocean) - Charlotte Eloise Stancioff; Robert Stojanov; Ilan Kelman; Daniel Němec; Jaromir Landa; Radomir Tichy; David Prochazka; Graeme Brown; Corinne L. Hofman (Atmosphere, 2018)
Small Island Developing States (SIDS) are now experiencing the local consequences of a changing climate, environment, and society. Nonetheless, climate change research frequently remains at regional or national levels. Without locally grounded data, islanders’ perceived impacts of the changes might not be considered, thereby causing difficulties when policy and practice responses are implemented without accounting for local understandings. To contribute to addressing this gap, this study examines perceptions of climate change and associated environmental and social changes in two SIDS case studies: St. Kitts in the Caribbean Sea and Malé Atoll, Maldives in the Indian Ocean. Through these two case studies, we assess perceptions of changing social and natural environments through a closed-question, face-to-face survey. Our results suggest that in both island case studies, communities perceive environmental changes to be happening that demand negotiation with the social changes of daily life. Results also suggest that perceived climate change impacts are only part of the equation, as social and economic impacts reveal two case studies of changing island societies. While the geographic context in each case study differs, this study reveals the perceived impacts of climate change and social changes at a local level, providing valuable insights and angles for formulating policies and actions to deal with the myriad of social and environmental changes affecting SIDS.